2014
DOI: 10.1002/glia.22740
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 increases microglia-mediated engulfment of apoptotic cells via upregulation of the milk fat globule-EGF factor 8

Abstract: Milk fat globule-epidermal growth factor-factor 8 (Mfge8) has been described as an essential molecule during microglia-mediated clearance of apoptotic cells via binding to phosphatidylserine residues and subsequent phagocytosis. Impaired uptake of apoptotic cells by microglia results in prolonged inflammatory responses and damage of healthy cells. Although the mechanisms of Mfge8-mediated engulfment of apoptotic cells are well understood, endogenous or exogenous factors that regulate Mfge8 expression remain el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…During classical microglial activation, LPS can significantly reduce MFGE8 expression (Fig 4C,D) while increasing phagocytic activity (Fig 4F). This is consistent with other past reports performed under WT conditions 18, 19, 20…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…During classical microglial activation, LPS can significantly reduce MFGE8 expression (Fig 4C,D) while increasing phagocytic activity (Fig 4F). This is consistent with other past reports performed under WT conditions 18, 19, 20…”
Section: Resultssupporting
confidence: 94%
“…It has also been shown to be a key regulator of C1q expression and synaptic pruning in the developing visual system 40. Besides, TGFb1 can also upregulate MFGE8 expression and increase microglia‐mediated engulfment of apoptotic cells 20. Hence, the increased TGFb signaling could potentially stimulate both C1q and MFGE8.…”
Section: Discussionmentioning
confidence: 99%
“…There are still controversial data concerning the protective/noxious role of MFG-E8. On one hand, MFG-E8 has been associated with microglia anti-inflammatory properties, as demonstrated by Spittau et al [75], when the cells were stimulated by TGF- β , in the MGF-E8 −/− mice showing an increased proinflammatory response [19], as well as in the septic mouse presenting downregulation of MFG-E8 levels [76]. On the other hand, Liu and colleagues [77] have demonstrated that MFG-E8 overexpression occurred concomitantly with TNF- α and IL-1 β upregulation.…”
Section: Discussionmentioning
confidence: 92%
“…TGFb is a known inducer of the M2c phenotype and it is released by many cell types in the brain but mainly by microglia (Spittau et al, 2015). By using antagonists for CB1 and CB2 receptors, we have seen by RT-PCR that SOCS3 induction by TGFb at 6 h post-treatment was blocked (Suppl.…”
Section: Cb1r and Cb2r Antagonists Block The Increase Of Arg-1 In M2amentioning
confidence: 94%
“…The acquired deactivated (M2c) phenotype is induced by the immunosuppressive cytokines, TGFb and IL-10, and it is mainly identified by the expression of SOCS3. Significantly, apoptotic cells are capable of enhancing microglial TGFb expression and release thereby shifting the microglia phenotype towards alternative activation M2c (Spittau et al, 2015). Indeed, it was recently reported that these phenotypes can be identified in microglia cultures (Chhor et al, 2013).…”
Section: Introductionmentioning
confidence: 98%